SISTEM INFORMASI UNTUK MENINGKATKAN KEDISIPLINAN SISWA (SI UMEKS) - Agus Suprianto, (JOEL: Journal of Educational and Language Research, 2022)
The student's violation points are displayed big in front of the hall, there are violation points in every class and even in the personality book, but there is no follow up. Junior high school is adolescent era. Adolescent is the search for personality era. Violations frequently happened. The lack of discipline. Discipline can help conducive study process. Discipline shows the dignity and prestige of human glory. Discipline can take someone's success in achieving their goals. Recording student violations can foster student discipline. The existence of information and communication technology needs to be used in this matter by creating an information system. This computer can generate reports that are fast, precise, and accurate. The results can be followed up by the counselling teacher by providing counselling guidance services.